2019
DOI: 10.1155/2019/8731705
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Mothers Have a Desire to Be Offered Professional Breastfeeding Support by Pediatric Nurses: An Evaluation of the Mother-Perceived-Professional Support Scale

Abstract: Background. Although the World Health Organization recommends exclusive breastfeeding for six months, the rate of breastfeeding has decreased worldwide. Breastfeeding is the natural way of feeding a baby, but it is a process that has to be learnt. It is not unusual for problems to occur and hence support for breastfeeding is vital. The aim of this study was to explore first-time mothers’ experiences of the breastfeeding support offered by pediatric nurses, as well as to develop and evaluate the Mother Perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
6
0
2
Order By: Relevance
“…If providers experience under-resourcing they make decisions about care priorities and breastfeeding support is not prioritised. These findings support the work of other studies linking understaffing and lack of time with lack of breastfeeding support provision [75,79,80] and women's perceptions that providers are unable to provide breastfeeding support due to a lack of time and resources within healthcare organisations [75,77]. Funding cuts to breastfeeding support services are therefore not only detrimental to women's breastfeeding experiences [81] but also detrimental to provider development.…”
Section: Plos Onesupporting
confidence: 81%
“…If providers experience under-resourcing they make decisions about care priorities and breastfeeding support is not prioritised. These findings support the work of other studies linking understaffing and lack of time with lack of breastfeeding support provision [75,79,80] and women's perceptions that providers are unable to provide breastfeeding support due to a lack of time and resources within healthcare organisations [75,77]. Funding cuts to breastfeeding support services are therefore not only detrimental to women's breastfeeding experiences [81] but also detrimental to provider development.…”
Section: Plos Onesupporting
confidence: 81%
“…The health worker dedicated to following the mother immediately after giving birth will determine the success of the effective promotion more than all the prenatal courses and information previously received. A study reports that when the pediatric nurses took time and booked extra appointments, the mothers felt supported [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parents desired professional and individualized instruction regarding infant feeding that was in keeping with their attitudes, beliefs, culture, and feeding decision from various sources [83], including physicians, pediatric nurses, lactation consultants, or professionals working in health care centers or public nutrition programs, described collectively here as health care providers (HCP). In contrast, studies illuminated that many parents found "infant feeding advice, support, and education from their HCP inadequate, missing completely, inconsistent or contradictory" [36][37][38]41,42,44,46,[49][50][51]53,55,57,63,72,74,76,83,97,98,103,104]. As identified within some studies, while it is important to promote and maintain BF, it is also necessary to ensure that the care, education, and needs of parents and their infants that are not BF are met [74,76], without stigmatizing parents who do not BF [68].…”
Section: Parent's Expectations Of Education and Support Addressing Pementioning
confidence: 99%